Bendamustine and rituximab combination is safe and effective as salvage regimen in Waldenström macroglobulinemia. Issue 9 (2nd September 2015) - Tedeschi, Alessandra; Picardi, Paola; Ferrero, Simone; Benevolo, Giulia; Margiotta Casaluci, Gloria; Varettoni, Marzia; Baratè, Claudia; Motta, Marina; Gini, Guido; Goldaniga, Maria Cecilia; Visco, Carlo; Zaja, Francesco; et al.
Abstract : According to the European Society for Medical Oncology and National Comprehensive Cancer Network guidelines on Waldenström macroglobulinemia, bendamustine (B) may be considered a suitable therapeutic option. To address the role of B in combination with rituximab (BR), we analyzed the outcome of 71 patients with relapsed/refractory disease, median age 72 years, treated with R 375 mg/m 2 day 1 and B days 1 and 2 (dosage ranging from 50 to 90 mg/m 2 ). Patients had previously received a median number of 2 lines of treatment (range 1–5). Overall and major response rates were 80.2% and 74.6%. Major toxicity was grade 3/4 neutropenia occurring in 13% of courses. There was no significant association between baseline features or patients' characteristics and response achievement. Median progression-free survival was not reached after a median follow-up of 19 months (range 3–54). None of the patients developed aggressive lymphoma or secondary myelodysplastic syndrome/acute myeloid leukemia. BR was found to be an active and well-tolerated salvage regimen leading to rapid disease control.